2014
DOI: 10.1080/01490451.2014.907379
|View full text |Cite
|
Sign up to set email alerts
|

Bio-precipitation of Calcite with Preferential Orientation Induced bySynechocystissp. PCC6803

Abstract: This article presents a research study on the deposition process of Ca 2C induced by Synechocystis sp. PCC6803 in BG11 liquid medium with different Ca 2C concentrations and different pH. The changes of Ca 2C concentrations were measured by using atomic absorption method and the corresponding dynamical models were studied. Minerals and cells were analyzed by high resolution transmission electron microscope, selected area electron diffraction, scanning electron microscope, energy dispersive X-ray spectroscope, X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 36 publications
1
23
0
Order By: Relevance
“…Samples were taken by immersing grids coated with a carbon film for 10 s in prepared bacterial suspension and dried several minutes at room temperature. The possible precipitated carbonate observed with TEM was further confirmed using Selected Area Electron Diffraction (SAED) (Han et al, 2014). …”
Section: Methodsmentioning
confidence: 90%
See 1 more Smart Citation
“…Samples were taken by immersing grids coated with a carbon film for 10 s in prepared bacterial suspension and dried several minutes at room temperature. The possible precipitated carbonate observed with TEM was further confirmed using Selected Area Electron Diffraction (SAED) (Han et al, 2014). …”
Section: Methodsmentioning
confidence: 90%
“…To measure the concentrations of Cd 2+ and Pb 2+ at the end of the incubation, the supernatant was collected by centrifugation (13400 × g , 2 min), and was digested completely and diluted with Milli-Q water. The concentrations of Cd 2+ and Pb 2+ in the solution were measured with an inductively coupled plasma source mass spectrometer (Optima 7300 DV, PerkinElmer) (Han et al, 2014). …”
Section: Methodsmentioning
confidence: 99%
“…Cyanobacteria have also been widely used as experimental strains to induce mineral precipitation. Han et al [18] reported a clear preferential orientation in the calcite induced by Synechocystis sp. PCC6803.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the contents of magnesium in carbonate (Young and Galy 2004). In low Mg/Ca ratio fluid, such as basin, swamp, Mg-calcite with equal size could be formed, while in high Mg/Ca ratio fluid, such as sea water or salty lake, high-Mg calcites and aragonite could often be formed (Bener et al 1975;Fernandez-Diaz et al 1996;Han et al 2014). …”
Section: Introductionmentioning
confidence: 97%
“…This microorganism itself and its extracellular polymeric substances (EPS) could be regarded as suppliers for nucleation sites, which had played an important role in mineral nucleation and Han et al (2014) found that the Synechocystis sp.…”
Section: Introductionmentioning
confidence: 99%